Modelling of a thermosyphon solar water heating system and simple model validation - Kalogirou, Soteris A.; Papamarcou, Christos (My University, 2000)
A thermosyphon solar water heater consisting of two flat plate collectors of total aperture area of 2.7 m2 and 150 l storage tank is modelled using TRNSYS. Simple experiments were conducted in order to validate the model. During the experiments weather conditions were measured every 10 min and integrated over an hour. The temperature of the water in the storage tank was also measured at the beginning and at the end of the day. The storage tank temperature rise was used to validate the model by using the actual weather data as input to the program. Validation tests were performed for 25 days spread over 6 months and the mean deviation between the predicted and the actual values of water temperature rise is 4.7% which is very satisfactory. Subsequently, long term system performance is estimated by using TRNSYS model run with the weather values of TMY file for Nicosia, Cyprus. The annual solar fraction obtained was 79% and the system could cover all the hot water needs of a house of four people during the three summer months. The maximum auxiliary energy was needed during the months of December and January (about 280 MJ/month). In addition, an economic analysis of the system was carried out. The pay-back time of the system was found to be 8 years and the present worth of life cycle savings was found equal to C£ 161.
Keywords: Thermosyphon solar water heater